PENGARUH VARIASI SUDUT NOZZLE DAN JUMLAH SUDU TERHADAP KINERJA TURBIN PELTON - Koswara, Engkos; Dewi Jannati, Eidelwei; Rachmat, Asep; Fudholi, Ahmad; Zauhari, Azi (J-ENSITEC, 2024)
In Indonesia, one of the government's programmes is village electricity. For remote villages in mountainous areas, the construction of micro-hydro power plants is one of the answers to the government programme. Power generation in this way is very suitable for our country, given the natural conditions consisting of many mountains that have streams of river water. In turbines we recognise various types of turbines used, we can use francis, kaplan and pelton turbines. The use of these turbines depends on the potential head owned, Pelton turbines that use the principle of impulse require a relatively high head. In this study, it will be studied how the effect of nozzle angle variation and the number of blades on the performance of pelton turbines. The test results show that the tilt angle 65° produces higher rotation at 900-910 rpm while the tilt 90° produces lower rotation around 800-880 rpm. While the effect of the number of blades used is not so significant in the performance of pelton turbines, it can be seen in the use of the number of blades 9 and 18 at the tilt 65° nominal rotation that occurs around 900-910 rpm.